Analisis Kesalahan Ejaan Yang Terdapat Di Rumah Sakit PKU Muhammadiyah Karanganyar Dan RSUD Kartini Karanganyar - Arfika Dhea Syaharani; Kundharu Saddhono (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Humans need language to be able to convey things to other living creatures. Each language reflects the unique worldview and understanding of the community that uses it. Language can be in spoken or written form. Written language has grammar and spelling rules that must be followed to ensure clear and consistent understanding between the writer and the reader. This research aims to analyze language errors found in public places and correct them based on appropriate grammatical rules. The descriptive qualitative method was chosen in carrying out this research so that knowledge and theories obtained through searching books, electronic books and journals are needed. Qualitative descriptive research analysis is directed at gaining knowledge or theory about research through journals and books. The method in this research also explores written material through literature review. This research uses data sourced from writings at the PKU Muhammadiyah Karanganyar Hospital and Kartini Karanganyar Regional Hospital and then analyzed according to applicable linguistic rules. Spelling analysis in this research uses EYD V and KBBI as references. Based on the analysis carried out, there were errors in writing non-standard words, italics, capital letters, writing the affix di-, and punctuation.